2009
DOI: 10.2522/ptj.20090058
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Manipulative Therapy Has an Immediate Effect on Thermal Pain Sensitivity in People With Low Back Pain: A Randomized Controlled Trial

Abstract: Inhibition of Adelta fiber-mediated pain perception was similar for all groups. However, inhibition of temporal summation was observed only in participants receiving SMT, suggesting a modulation of dorsal horn excitability that was observed primarily in the lumbar innervated area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 71 publications
5
133
0
Order By: Relevance
“…6,21,29 Recently, Bialosky et al 4 suggested that the placebo effect may also be part of the mechanism of manual therapy, and that the failure of a manual therapy intervention to perform better than a placebo does not necessarily indicate a failed intervention, if both outperform the natural history of the condition. The present study was not able to include a nontreatment group by which to compare the natural history of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…6,21,29 Recently, Bialosky et al 4 suggested that the placebo effect may also be part of the mechanism of manual therapy, and that the failure of a manual therapy intervention to perform better than a placebo does not necessarily indicate a failed intervention, if both outperform the natural history of the condition. The present study was not able to include a nontreatment group by which to compare the natural history of the condition.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated increased sensitivity to mechanical stimulation and receptive field expansion in dorsal horn neurons following injection of bradykinen into the lumbar multifidus [69,70]. By recording pain threshold following repeated stimuli to peripheral C-fibers, a number of studies have also reported wind-up related, central sensitization in patients with low back pain [71][72][73] TMJ pain [74] shoulder pain [75] and fibromyalgia [76]. Subacute or chronic C-fiber mediated pain increases the release of glutamate and substance-P from sensory afferents in spine, leading to hypersensitivity of second order, dorsal horn neurons.…”
Section: The Transition Of Peripheral Pain To Central-mediated Chronimentioning
confidence: 99%
“…The publication of 'guidelines for the management of LBP' recommends the use of MT and exercise for the condition (CSP, 2006;van Tulder et al 2006;Savigny et al, 2009 andChou et al, 2009). Furthermore, these guidelines are supported by studies demonstrating clear patient-reported benefits (Goodsell et al, 2000, Bialosky et al 2009band van Middelkoop et al, 2011. However, there continues to be debate within the literature regarding how best to quantify effects and how to determine the magnitude and the clinical significance of observed treatment responses (Potter et al 2005;Theodore, 2010).…”
Section: Introductionmentioning
confidence: 99%